2004
DOI: 10.1016/j.jasms.2003.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Arrhenius activation parameters for the loss of neutral nucleobases from deprotonated oligonucleotide anions in the gas phase

Abstract: Arrhenius activation parameters (E a and A) for the loss of neutral nucleobase from a series of doubly deprotonated oligodexoynucleotide 10-mers of the type XT 9 , T 9 X, and T 5 XT 4 , where X ϭ A, C, and G, have been determined using the blackbody infrared radiative dissociation technique. At temperatures of 120 to 190°C, the anions dissociate exclusively by the loss of a neutral nucleobase (XH), followed by cleavage of the sugar 3Ј C™O bond leading to (a-XH) and w type ions or, in the case of the T 9 X 2Ϫ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The authors found that the loss of a nucleobases is sensitive to its identity and location in the oligodeoxynucleotide, and found a trend in the values of Ea: A<G<C. They pointed that the differences observed in Ea comes not only from the bases identity but also from the ability of the nucleobases to participate in intramolecular interactions. 53,54 Infrared multiple photon dissociation (IRMPD) can also be used in a similar way to BIRD, provided that slow heating conditions (slower dissociation rates than photon absorption/emission rates) are maintained. 55 IRMPD was recently applied to megadalton-sized DNA; note however the dissociation rates were quite fast.…”
Section: Iii22 Ms/ms For Direct Gas-phase Structural Probing By Slmentioning
confidence: 99%
“…The authors found that the loss of a nucleobases is sensitive to its identity and location in the oligodeoxynucleotide, and found a trend in the values of Ea: A<G<C. They pointed that the differences observed in Ea comes not only from the bases identity but also from the ability of the nucleobases to participate in intramolecular interactions. 53,54 Infrared multiple photon dissociation (IRMPD) can also be used in a similar way to BIRD, provided that slow heating conditions (slower dissociation rates than photon absorption/emission rates) are maintained. 55 IRMPD was recently applied to megadalton-sized DNA; note however the dissociation rates were quite fast.…”
Section: Iii22 Ms/ms For Direct Gas-phase Structural Probing By Slmentioning
confidence: 99%
“…Ac opper shield, which is cooled by liquid nitrogen to T % 80 K, surrounds the cell [88,89] to minimize the amount of black body infrared radiative dissociation (BIRD). [90][91][92][93][94][95][96][97][98][99] From the rear side of the magnet, at unable IR OPO laser system (EKSPLA NT273-XIR) is coupled into the cell through aC aF 2 window. [100] When absorption events lead to photodissociation, [101] they are detected by the experiment.…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…These ions are guided through a system of electrostatic lenses passing three differential pumping stages to the center of the ICR cell where they are stored and mass selected in a 4.7 T magnetic field under ultra‐high vacuum (≈10 −10 mbar) conditions. A copper shield, which is cooled by liquid nitrogen to T ≈80 K, surrounds the cell to minimize the amount of black body infrared radiative dissociation (BIRD) …”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…Absolute rate coefficients k abs are obtained by analyzing the pseudo-first-order kinetic plots of different experimental runs taken over a range of pressures. The cluster distribution shrinks due to blackbody infrared radiative dissociation (BIRD) 6876 and the exothermicity of the reaction. 58,77,78 The error of the rate coefficient was estimated to be about 30% due to the uncertainty of the pressure calibration.…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%